(untitled) - Hirsch, Yale (Hoboken, N.J., 2006)
This time-tested guide to stock trading, published every year since, 1968, is a practical investment tool with a wealth of information organized in a calendar format. You'll learn about little-known market patterns and tendencies that will help you forecast market trends with accuracy and confidence. The data in the Almanac is some of the cleanest in the business, and its analyses are relied upon by savvy professionals, from well-know money managers to journalists. As always, the Almanac encapsulates all the historical price information on the stock market, provides monthly and daily reminders, and alerts users to seasonal opportunities and dangers. In addition, this mid-term election edition focuses heavily on the presidential election cycle and tendencies often resulting in major market moves.
Keywords: Stocks,Stock exchanges,Investment analysis